PENGGUNAAN SISTEM INFORMASI GEOGRAFIS (SIG) DALAM ANALISIS DAYA DUKUNG DAN DAYA TAMPUNG LINGKUNGAN HIDUP DI KABUPATEN TANAH LAUT - Muhammad Syahirul Alim (Universitas Lambung Mangkurat, 2019)
The objective of the study was to provide an overview of the using of Analytical Geographical Information System (GIS) to determine Environmental Carrying Capacity and Capability in Tanah Laut Regency Province of South Kalimantan. The combination methode of Pairwise Comparation and The spatial capacity offered by GIS is directly applicable to understanding the spatial variation by environmental factors. The result of this study shows that carrying capacity and capability can reflect a potential and availability of natural resources in the area of Tanah Laut Regency so that it can be known in which areas have the greatest potential and availability of indicators where the percentage distribution of the extent of the environmental carrying capacity of each ecosistem service potential and the most dominant availability are in the District of Jorong, which is 60% for the High category including 6 Ecosistem Services and 40% for the very high category for 4 Ecosistem Services. 30% Kintap Subdistrict for very high category for 3 Ecosistem Services and 20% for High category includes 2 Ecosistem Services.